Marriage and Family Therapy: When To Go/How To Find One - Donna Davis; Suzanna Smith (EDIS)
FAR-3000, a 2-page transcript of the radio broadcast by Donna Davis and Suzanna Smith, provides an introduction to marriage and family therapy and how it works. Includes links to sounds files of the radio broadcast. Published by the UF Department of Family Youth and Community Sciences, August 2006.